2020
DOI: 10.1007/s11060-020-03605-6
|View full text |Cite
|
Sign up to set email alerts
|

Glioma consensus contouring recommendations from a MR-Linac International Consortium Research Group and evaluation of a CT-MRI and MRI-only workflow

Abstract: Introduction This study proposes contouring recommendations for radiation treatment planning target volumes and organs-at-risk (OARs) for both low grade and high grade gliomas. Methods Ten cases consisting of 5 glioblastomas and 5 grade II or III gliomas, including their respective gross tumor volume (GTV), clinical target volume (CTV), and OARs were each contoured by 6 experienced neuro-radiation oncologists from 5 international institutions. Each case was first contoured using only MRI sequences (MRI-only)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…This would be possible by incorporating into our analysis, the quantitative T1, T2, MT data acquired on separate days as part of our larger multi-parametric imaging protocol [32]. CEST parameters within the GTVs were used, but quantification in tumour ROIs that have more spatially homogeneous signals (e.g., in core, peripheral or FLAIR hyperintense regions) can be considered [28,41,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…This would be possible by incorporating into our analysis, the quantitative T1, T2, MT data acquired on separate days as part of our larger multi-parametric imaging protocol [32]. CEST parameters within the GTVs were used, but quantification in tumour ROIs that have more spatially homogeneous signals (e.g., in core, peripheral or FLAIR hyperintense regions) can be considered [28,41,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies had shown a potentially positive impact on survival in patients undergoing supratotal resection or "FLAIRectomy" [22,23]. Another potential application for the current study will be in guiding RT target volumes, speci cally targeting areas of in ltrative tumor, as the standard practice includes a wider margin in an empirical manner [24]. Identifying and excluding areas of reactive edema with a lower likelihood of microscopic disease from the target volumes can help reduce treatment toxicities and adopt individualized target volumes.…”
Section: Discussionmentioning
confidence: 98%
“…Delineation of OARs, gross tumor volume (GTV), and clinical target volume (CTV) were de ned based on glioma consensus contouring guidelines [22]. Planning target volume (PTV) was generated as a 0.4-cm isotropic expansion of the CTV.…”
Section: Radiotherapy Simulation and Target De Nitionmentioning
confidence: 99%